The application of three-dimensional radar display for holding stack management - Tan, Alicia Jia Yi (2018)
As air traffic demand continue to grow in the upcoming years, Air Traffic Management (ATM) are being challenged to provide safe and orderly flight in the sky for the same amount of resources. Many automation tools had been implemented to aid Air Traffic Control Officers (ATCOs) and pilots for safer and a more sophisticated way of managing traffic. However, this gives the ATCOs less control in authority as it encourages high reliance on the system. Thus, advancement in technology would be insufficient to combat the growing air traffic demand to reduce ATCOs cognitive workload. Possible errors in ATC such as issuing wrong commands and heading lead to extra work being done to rectify the situation. This is especially serious in the event of high density volume traffic, which causes additional workload on the ATCOs, hence deteriorating their performance. Therefore, a three-dimensional display was proposed to provide a clearer and less dense information display for ATCOs, which aims to reduce their cognitive workload demand during high density traffic. EEG-based and NASA-TLX questionnaires will be used to measure the physiological workload and subjective workload of the subjects respectively. This report will provide results and findings of the workload that the subjects experienced and their performance, comparing between 2D and 2D+3D display experiment. Overall, the implementation of 2D+3D display results suggest a reduction in workload of the ATCOs, however performance in fuel burn and radio telephony was lower.